Memberikan Motivasi Untuk Memulihkan Kondisi Perekonomian Seorang Pedagang Kecil Akibat Dampak Pandemi Covid - 19 - IRFAN FAHREZA; Husni Thamrin (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Covid-19 pandemic is an epidemic that occurs in various parts of the world. The impact caused by the pandemic is felt by all citizens in various countries. The Covid-19 pandemic is not only disturbing health, but has an impact on the economic order of all countries. The country's economic condition since March 2020 has plummeted, this can be seen from the recorded Gross Domestic Product (GDP) growth of -2.07% in 2020, whereas in 2019 GDP still grew to 5.02%. The decline in economic growth was also felt by small traders such as a resident who made a living as a flower seller in the city of Tebing Tinggi. The solutions offered in practical activities are several ways that the florist can do to increase his income. The stages used in the micro-level social intervention are the case work stages of skidmore which consist of the assessment stage, program planning, intervention stage, evaluation stage, and termination stage. In the study phase, I as a case woker began to build relationships with clients. At the case woker stage, I tried to explain and instill the understanding that it is the client who determines the results to be achieved later. In the case study stage the woker tries various forms of therapy (treatment), depending on the client's needs. The intervention phase is basically developed based on the client's needs. In this case the case woker can discuss choosing alternative solutions to problems with the client, the client is encouraged to develop his ability to overcome the problems he faces. While the termination stage is the stage where the relationship between the case woker and the client will be terminated. Termination can be stopped if it is seen that there is a change in the client for the better.